Photosynthetic responses and proline content of mature and young leaves of sunflower plants under water deficit - Cechin, Inês [UNESP]; Rossi, S. C. [UNESP]; Oliveira, V. C. [UNESP]; Fumis, Terezinha de Fátima [UNESP] (Institute of Experimental Botany, 2006)
In mature and young leaves of sunflower (Helianthus annuus L. cv. Catissol-01) plants grown in the greenhouse, photosynthetic rate, stomatal conductance, and transpiration rate declined during water stress independently of leaf age and recovered after 24-h rehydration. The intercellular CO 2 concentration, chlorophyll (Chl) content, and photochemical activity were not affected by water stress. However, non-photochemical quenching increased in mature stressed leaves. Rehydration recovered the levels of non-photochemical quenching and increased the F v/F m in young leaves. Drought did not alter the total Chl content. However, the accumulation of proline under drought was dependent on leaf age: higher content of proline was found in young leaves. After 24 h of rehydration the content of proline returned to the same contents as in control plants.
Keywords: Chlorophyll; Drought; Intercellular CO 2 concentration; Leaf water potential; Non-photochemical quenching; Photochemical activity; Rehydration; Stomatal conductance to water vapour; Transpiration rate; Helianthus; Helianthus annuus